KNOWLEDGE AND ATTITUDE ON CHILDHOOD HEARING LOSS AMONG MOTHERS AND MOTHERS-TO-BE IN AN URBAN AREA OF MALAYSIA - Ai, Wong Yun; Mukari, Siti Zamratol-Mai Sarah; Harithasan, Deepashini; Mazlan, Rafidah (International Journal of Allied Health Sciences, 2019)
Introduction: Parental knowledge and attitude on hearing loss play an important role on early diagnosis and effective intervention of childhood hearing impairment. This study aimed to 1) assess the knowledge and attitude on childhood hearing loss, and 2) to examine the relationship between knowledge and attitude among mothers and mothers-to-be in an urban area of Malaysia. Methods: A cross sectional survey was conducted on 181 mothers and mothers-to-be (mean age: 32.2 Â± 4.6 years, range: 20-47 years old) who attended Obstetrics & Gynaecology Clinic at Hospital Universiti Kebangsaan Malaysia (HUKM). We interviewed the participants using a newly developed and validated questionnaire. Level of knowledge and attitude were classified into highly satisfactory (>80%), satisfactory (61-80%), sufficient (41-60%), insufficient (21-40%) and highly insufficient (â‰¤20%). Results: The mean score for knowledge is 71.4%. The level of knowledge was satisfactory in the majority of the participants (74%), whereas in 13.3% and 12.7% the level was sufficient and highly satisfactory, respectively. The knowledge in causes of hearing loss is highest for head injury (91.7%) while lowest for measles (29.3%). The majority of the participant showed satisfactory of attitude towards childhood hearing loss (61.9%), in 27.1% the level of attitude was highly satisfactory and in 11% sufficient. There was no relationship between knowledge and attitude on childhood hearing loss. Conclusions: There is a need to carry out more awareness program to improve the knowledge and attitude of mothers and mothers-to-be so that it will translate into early identification and more effective intervention of childhood hearing loss.